Executive Guide to Speech-Driven Computer Systems - McPherson, Malcolm (Executive Guides., 1995)
A new generation of speech-driven personal computer systems promises to transform the business use of Information Technology. This is not merely a matter of discarding the keyboard, but of rethinking business processes to take advantage of the increased productivity that speech-driven systems can bring. Malcolm McPherson is one of the pioneers of this fast-moving field, and has been personally involved in the development of systems that have met business needs across many industrial sectors.